Isolation of intake mediated effects demonstrate that the phenomic benefits of dietary omega-3 are nominal to Atlantic salmon when reared in a challenging (hypoxic) environment - Brett D. Glencross; Alex Berry; Ben Clokie; Ernst Hevroy; David Huyben; Laura Martinez-Rubio; Chessor A. Mathew; Pedro Munoz; Simon MacKenzie; Rod W. Wilson (Aquaculture, 2024)

Auditory predator cues decrease herbivore survival and plant damage - Zachary A. Lee; Caroline B. Cohen; Alex K. Baranowski; Kristen N. Berry; Maxwell R. McGuire; Tyler S. Pelletier; Brendan P. Peck; Jacqueline J. Blundell; Evan L. Preisser (Ecology, 2023)
The high fitness cost of predation selects prey capable of detecting risk cues and responding in ways that reduce their vulnerability. While the impacts of auditory predator cues have been extensively researched in vertebrate prey, much less is known about invertebrate species' responses and their potential to affect the wider food web. We exposed larvae of Spodoptera exigua , a slow‐moving and vulnerable herbivore hunted by aerial predators, to recordings of wasp buzzing (risk cue), mosquito buzzing (no‐risk cue), or a no‐sound control in both laboratory and field settings. In the laboratory, wasp buzzing (but not mosquito buzzing) reduced survival relative to the control; there was, however, no effect on time to or weight at pupation in survivors. In the field, wasp buzzing reduced caterpillar herbivory and increased plant biomass relative to the control treatment. In contrast, mosquito buzzing reduced herbivory less than wasp buzzing and had no effect on plant biomass. The fact that wasp cues evoked strong responses in both experiments, while mosquito buzzing generally did not, indicates that caterpillars were responding to predation risk rather than sound per se. Such auditory cues may have an important but largely unappreciated impacts on terrestrial invertebrate herbivores and their host plants.

Ship-Based Contributions to Global Ocean, Weather, and Climate Observing Systems - Shawn R. Smith; Gaël Alory; Axel Andersson; William Asher; Alex Baker; David I. Berry; Kyla Drushka; Darin Figurskey; Eric Freeman; Paul Holthus; Tim Jickells; Henry Kleta; et al. (Frontiers in Marine Science, 2019)

Connexin 50 mutation in a family with congenital "zonular nuclear" pulverulent cataract of Pakistani origin - Vanita Berry; Donna Mackay; Shagufta Khaliq; Peter J. Francis; Abdul Hameed; Khalid Anwar; S. Qasim Mehdi; Richard J. Newbold; Alex Ionides; Alan Shiels; Tony Moore; Shomi S. Bhattacharya (Human Genetics, 1999)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)